Development of a patient‐reported experience measure for chronic inflammatory skin diseases. (25th February 2022) - Van den Steen, E.; Ramaekers, D.; Horlait, M.; Gutermuth, J.
Abstract: Background: Patient involvement and high‐quality patient‐provider interactions are critical factors for quality of care in chronic inflammatory skin diseases. Also, assessing the patient's perspective contributes to optimizing care delivery and patient's experience. Until today, no user‐friendly tools to measure patient experiences exist within immunodermatology. Objectives: The aim of this study was to identify the relevant items for patient's experience in immunodermatology and develop a concise questionnaire to assess patient's experience in routine clinical care. Methods: Potential relevant items for measuring patient's perspective of immunodermatology care were identified by a literature search. From this longlist, a shortlist from patient's perspective was distilled by semi‐structured interviews with a diverse patient group. This list was reduced to final items using a modified Delphi method in a multi‐stakeholder focus group. For each item, one question was formulated to generate the Patient‐Reported Experience Measure (PREM) questionnaire. A first internal validation was achieved by an email round. Results: Forty longlist items were categorized into five domains (access to care, patient centeredness, access to information, care process and satisfaction). During interview rounds, 19 shortlist items were selected if mentioned by ≥40% of interviewees. Via the focus group, the most important items were chosen by participant consensus. For each item, a question was formulated. The final PREM covers 11 items (plus 2 in case of a first consult). The first internal validation showed that the tool is clear, understandable and has an ideal length. Conclusion: This short user‐friendly PREM can be used in scientific and routine settings to improve care for patients who suffer from chronic inflammatory skin diseases. Abstract : Linked Commentary: A.‐H. Fink‐Wagner. J Eur Acad Dermatol Venereol 2022; 36 : 767–768. https://doi.org/10.1111/jdv.18153 .